A Study on the Factors Affecting usage of Voice Assistants and the Interface Transition from Touch to Voice - Karthik Santhanaraj, Dr. Barkathunissa A (International Journal of Advanced Science and Technology, 2020)
The interface simplicity has always been one of the most important factors which makes any new technology or device successful. Once an individual gets attached to a particular interface it becomes easy for them to use any devices which follows the same interface pattern. But to adapt to a new interface for the same device or the same need it will take a lot of effort from both the user and the companies which advances those to support each other to make the interface shift happen. The timespan required for this interface shift depends on the mindset of each individual and the simplicity of the proposed interface. Voice Assistants (VA) are an important achievement, which have become an inseparable and integral part of many smart devices. The mobile penetration in India has allowed rapid acceleration among metropolitan Indian adults in the usage of the wearable devices and other such smart technologies. Voice as an interface is going to improve the next generation of social conversation, content searches and medium of commerce. The rapidly increasing competition in this segment has led to several improvements. We already have many such voice-enabled devices that help us to set routines, automate the home appliances and provides us on-demand information. Also, the smart speaker’s category in Indiagrew 43 per cent in the second quarter of 2018.Many big corporates like Amazon, Apple, Google and Microsoft offers an entire digital platform infrastructure that can be controlled by voice assistants. The future of Voice Assistants depends to a large extent on how natural and fluid the communication with the user can take place. The interface transition from touch to voice has several factors involved in it. This study is majorly to find out what are the major factors which are influencing this transition and how relevant are these identified factors for the transition to happen in Indian market. Keywords: Voice Assistants, Interface, Barriers, Transition, Touch to voice, Voice Inputs and Outputs.